An investigation of citizen intention to adopt e-participation in Malaysia e-government services / Laila Abdul Hamid - Abdul Hamid, Laila (2017)
Over the past decades, governments around the world have sought to capitalize on technology, communications (ICT) and to improve their services to the citizen. E Government has grown into a main focal point of government effort around the universe. Many countries have taken over and implemented e-government systems and services in their state. E-government services also has been introduced to Malaysia citizens. Although e-government aims to improve their services to citizens, there is still low e-government use among Malaysians. E-government should be broadened to include an e - participation mechanism to take people's opinions and input on government policies and programs for better information transmission. Utilizing the wide embrace of e-participation opportunities can help make online services more user-centric. The experience of various high-performance countries in the area, as considerably as those countries that deliver significantly improved their situation, indicating that long-term strategic planning and a holistic e-government brings real results. The objectives of this study are to identify and study the factors of intention to adopt e-participation in e-government services among citizen in the Klang Valley, Malaysia. The importance of this study is to assist the government in identifying the factors that affect the intention to use e-participation in e-government among citizens and to give a better understanding to citizens in adopting e participation. The research model was adapted from the Unified Theory of Acceptance and Use of Technology (UTAUT) model. UTAUT is one of the Theory Acceptance Test Model to determine the factors that cause the intention of using technology. This study was conducted amongst citizens in the Klang Valley, Malaysia. The data collected were analysed using SPSS. Regression analysis shows the Performance Expectations, Effort Expectations, Social Influences and Facilitating Condition have a positive influence on the intention to use e-participation. This study also determines the limitations and future recommendations in e-participation.